Domain dynamics of phase-separated lipid membranes under shear flow. Issue 47 (24th November 2022) - Hamada, Tsutomu; Mizuno, Shino; Kitahata, Hiroyuki
Abstract : Under external flow, phase-separated lipid vesicles exhibit localization dynamics of lateral domains. The localization pattern depends on the cholesterol content of the membrane. Abstract : The dynamical behaviour of lateral domains on phase-separated lipid vesicles under external flow is reported. A microfluidic chamber was used for the immobilization of vesicles and the application of shear. Microscopic observation revealed that domains tended to be localized at the vortex center and to exhibit a stripe morphology as the flow speed increased. We clarified the dependency of domain behaviors on the flow speed and lipid mixing fraction. The cholesterol ratio in the membrane affected these domain behaviors. Next, we investigated the growth of domains under flow. We discuss the mechanism of these trends by considering the free energy of phase separation, and reproduce the experimental results by numerical simulations. These findings may lead to a better understanding of the dynamical properties of the membrane under nonequilibrium situations and the biophysical mechanism of cellular mechanotransduction.